Comparison of losses and flux distribution in 3 phase 100 kVA distribution transformers assembled from various type of T-Joint geometry - Ismail, Daut; Dina Maizana, Maiz Ahmad; Shuhaimi, Zakaria; S. Uthman; Soib, Taib (Science Publications, 2008)
Link to publisher's homepage at http://scipub.org/scipub/index.php